(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
Until the 1800s, art historians considered the Venetian artist Carlo Crivelli (circa 1435– 1495) to be a secondary if not a minor painter. This lack of recognition stems essentially from the dissemination of his paintings in churches and convents throughout the provincial region of Marche (central-eastern Italy), where Crivelli spent the most productive period of his life from 1468 until his death in 1495. As a consequence of this limited accessibility, his paintings could not be seen by mainstream art dealers and historians such as the scrupulous Giorgio Vasari (1511–1574). More than anybody else, the British demonstrated a great interest in Crivelli’s art in the late 1800s by acquiring many of his dispersed Earth Sciences History Vol. 43, No. 2, 2024 pp. 303–326 paintings that eventually ended up in the National Gallery of London, where the richest collection of the artist’s paintings is preserved today. Among them, ‘The Vision of the Blessed Gabriele’ is the one that attracted our attention not so much for its pictorial qualities and symbolic significance typical of Renaissance paintings, but rather for the many details making up the background of the painting, which accurately depicted the geological and environmental characteristics of the Adriatic port city of Ancona and the nearby Monte Cònero mountain. In this research, besides a meticulous study of architectural, geomorphologic, faunal, and floral details, we focused on the representation of a large outcrop of strikingly pink, thinly stratified rocks, which we studied through a quantitative RGB (red, green, blue) chromatic analysis and then compared the results with those from an analogous analysis of rock samples and outcrop images of all the more-or less red formations of the Umbria-Marche lithostratigraphic succession. This led us to the conclusion that Crivelli’s pink rocks represent the lower Paleogene Scaglia Rossa limestone exposed at Monte Cònero. Thus, the background of Crivelli’s painting ‘The Vision of the Blessed Gabriele’ is no longer an idealized landscape put there as a symbolic or simple wing of a theater stage, but a realistic representation of the physical environment surrounding the main subject of the painting as only a few Renaissance maestros like Piero della Francesca, Andrea Mantegna, and Leonardo da Vinci incorporated in their most famous and studied masterpieces.